2020
DOI: 10.3390/biom10060864
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Determines Strain-Dependent Secondary Metabolite Production in Streptomyces venezuelae Strains

Abstract: Streptomyces venezuelae is well known to produce various secondary metabolites, including chloramphenicol, jadomycin, and pikromycin. Although many strains have been classified as S. venezuelae species, only a limited number of strains have been explored extensively for their genomic contents. Moreover, genomic differences and diversity in secondary metabolite production between the strains have never been compared. Here, we report complete genome sequences of three S. venezuelae strains (ATCC 10712, ATCC 1059… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 62 publications
3
17
1
Order By: Relevance
“…To date, 29 Streptomyces have been categorized as S. venezuelae strains on the basis of the similarity in their morphology and carbon utilization ( Ehrlich et al., 1948 ; Probst et al., 1965 ; Kim et al., 2020 ). In order to reassess this classification, we first compared phenotypic characteristics of ten S. venezuelae strains commercially available from ATCC (listed in Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, 29 Streptomyces have been categorized as S. venezuelae strains on the basis of the similarity in their morphology and carbon utilization ( Ehrlich et al., 1948 ; Probst et al., 1965 ; Kim et al., 2020 ). In order to reassess this classification, we first compared phenotypic characteristics of ten S. venezuelae strains commercially available from ATCC (listed in Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…On average, approximately 30 secondary metabolite biosynthetic gene clusters (smBGCs) are encoded in each Streptomyces genome, and most of these smBGCs are species-specific ( Omura et al., 2001 ; Bentley et al., 2002 ). Moreover, recent genome mining studies have shown high chemical diversity even within closely related Streptomyces strains ( Seipke, 2015 ; Antony-Babu et al., 2017 ; Park and Andam, 2019 ; Sottorff et al., 2019 ; Belknap et al., 2020 ; Kim et al., 2020 ), thereby emphasizing the importance of genome mining at the strain level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by W. Kim et al [6] explores complete genome sequences of three S. venezuelae strains (ATCC 10712, ATCC 10595, and ATCC 21113) harboring chloramphenicol and jadomycin BGCs. The high-quality genome sequences exhibited that the three strains share more than 85% of total genes, including most of the SM BGCs.…”
mentioning
confidence: 99%